FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN TERHADAP PEMBELIAN MINYAK GORENG KEMASAN PADA SAAT MASA COVID DI KOTA TASIKMALAYA - Ruri Abdul Gani; Dona Setia Umbara; Reni Hidayati (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Cooking oil is one of the products derived from palm oil and is needed in everyday life. This product is one of the nine food staples consumed by almost all Indonesian people. The scarcity that occurred last year is a new momentum felt by the community, especially in the City of Tasikmalaya. There was a scarcity that caused the staple cooking oil to not be available in traditional markets or in supermarkets. The analytical tool used is multiple regression using 100 research samples. The results of this study state that those that have a significant influence on consumer decisions are product quality, product characteristics, product design, product packaging, product labels that have a significant effect on consumer decisions, while those that do not influence consumer decisions on packaged cooking oil During The Covid-19 in The Tasikmalaya City are product brands and product price, has no significant effect on consumer decisions. However, if it is carried out simultaneously, product quality, product characteristics, product design, product branding, product packaging, product labels and product prices have a significant influence on consumer decisions with an overall influence of 62.1%.